PHYSICAL THERAPY INTERVENTION FOR A PATIENT WITH POST-SURGICAL SHOULDER CAPSULORRHAPHY (International Journal of Physiotherapy, 2018)
Background: Posterior shoulder capsulorrhaphy is a surgical procedure to help restore shoulder joint stability in patients with a history of recurrent shoulder dislocations. Physical therapy (PT) may be beneficial in outpatient rehabilitation to improve patient shoulder range of motion (ROM), muscular strength, endurance, joint stability, and return to prior level of activities after general shoulder surgery. The purpose of this case study was to describe PT intervention for a patient with shoulder posterior capsulorrhaphy in an outpatient setting.Methods: 21-year-old male with post-surgical right shoulder posterior capsulorrhaphy due to multiple posteriorshoulder dislocation. Patient’s impairments were right shoulder weakness, decreased ROM, and functional immobility due to pain and a retracted capsule. PT intervention was 2-3X per week for nine weeks and included therapeutic exercises, manual therapy, modalities, and patient education for a home exercise program (HEP).Results: Patient was seen for 13 visits in an outpatient PT setting which improved his shoulder active ROM, strength, and outcome measures. The pain was also reduced. He returned to work with light duty restrictions after the 3rd week of PT and was able to perform normal responsibilities by the 9th week. He achieved the majority of his goals.Conclusion: PT intervention may have accelerated the progression of patient’s functional mobility, strength, ROM, and reduction of pain. Compared to the currently available literature for this diagnosis, the patient returned to normal function three weeks earlier than normal, probably due to earlier internal rotation exercise. Future research should include a randomized control trial regarding effective PT interventions following shoulder capsulorrhaphy surgery.